An exploratory study on counterfeit purchase intention of international brands amongst Malaysians. - Mah, Pei See (2001)
Counterfeit merchandise has become one of the most prosperous business in the country. Trade in counterfeit amounts to millions of ringgit each year, though providing the nation many opportunities in employment and trade, it also bring various adverse effects to an increasing number of industries. Counterfeit merchandise not only cuts into profits of the original brand manufacturers, but it also harms the brands' equity and the owners' reputation. The purpose of this study was to test the conceptual model of consumers counterfeit purchase intention for international brands. This study also attempt to explore the possibility of counterfeits devaluing the original brands. Over the years, counterfeit manufacturers and merchants have been blamed for illegally replicating and selling products of famous brands. This is only the supply side of the whole counterfeit trade. The economic theory always suggests that there is supply when demand occurs. Hence, it is necessary to understand the reasons behind the demand for counterfeits. Putting price aside, this study uses a non-price conceptual model, which includes the psychographics, product-attribute, and demographic variables. The ultimate goal is to explore the possible relationship between these constructs with the counterfeit purchase intention represented by the number of counterfeit items had been purchased by the respondents. Convenient survey technique, regression, and descriptive analyses were deployed. Implications of the study were also discussed in the final section of this study.